1995
DOI: 10.3758/bf03198940
|View full text |Cite
|
Sign up to set email alerts
|

One-trial context fear conditioning as a function of the interstimulus interval

Abstract: In two expertments, we examined the effects of a wide range of interstimulus intervals (2.5, 15,45, 120,135, and 405 sec) on one-trial context fear conditioning with rats. Here, the interstimulus interval (ISI) denotes the time between placement in a conditioning chamber and the onset of a single footshock. On the conditioning day, we observed that the rats' behavior at the time of shock onset varied systematically across lSI values. On the subsequent test day, we used context-evoked freezing as a measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
68
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 26 publications
17
68
0
Order By: Relevance
“…2A -D). Consistent with a variety of other studies demonstrating the immediate shock deficit (Blanchard et al 1976;Fanselow 1986Fanselow , 1990Kiernan and Cranney 1992;Westbrook et al 1994;Bevins and Ayres 1995), the shortest preshock interval (2 sec) produced very low levels of freezing in the context test regardless of the postshock duration ( Fig. 2A; F (1,15) ¼ 0.01).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…2A -D). Consistent with a variety of other studies demonstrating the immediate shock deficit (Blanchard et al 1976;Fanselow 1986Fanselow , 1990Kiernan and Cranney 1992;Westbrook et al 1994;Bevins and Ayres 1995), the shortest preshock interval (2 sec) produced very low levels of freezing in the context test regardless of the postshock duration ( Fig. 2A; F (1,15) ¼ 0.01).…”
Section: Resultssupporting
confidence: 76%
“…Wiltgen et al (2001) showed that a preshock interval as short as 5 sec produces appreciable levels of conditioned freezing, particularly during the first 2 min of the test session. Similarly, Bevins and Ayres (1995) observed robust freezing after a 2.5-sec preshock interval. The minimum amount of preshock context exposure required for CFC may vary across species and mouse strain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…* indicates signifi cant difference (p < 0.05) compared to hypothetical value of 0.5 (i.e., no preference). ulus interval have been as varied as eye-blink conditioning in humans (McAllister, 1953), aversive conditioning in goldfi sh (Bitterman, 1964), key-peck autoshaping in pigeons (Gibbon et al, 1977), context fear conditioning in rats (Bevins and Ayres, 1995), nicotine-conditioned hyperactivity in rats , and ethanol place conditioning in mice (Cunningham et al, 1997). The present research extended this list to include place conditioning with IV administered nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, temporally specific CRs have been observed in fear-potentiated startle after a single training experience (Davis et al 1989), and a similar temporal specificity as a function of training parameters has been replicated for different CRs in CFC (Bevins and Ayres 1995).The aim of Experiment 1 was to establish two different temporal predictions about US arrival, as a necessary step to test our hypotheses concerning the role of US temporal prediction error in memory destabilization-reconsolidation. Rats were trained with 1 and 5 min of context exposure prior to shock presentations, and tested 72 h later during 6 min in the training context, without shock.…”
Section: Methodsmentioning
confidence: 99%